The pro- and anti-cancer effects of oxycodone are associated with epithelial growth factor receptor level in cancer cells. Issue 2 (7th February 2020) - Yu, Yuqin; Li, Dapeng; Duan, Ji'an; Xu, Hongshuang; Li, Li; Tan, Dengwu; Yan, Hong
Abstract: Background: Oxycodone is an opioid medication used for the treatment of pain in cancer patients. However, little is known on the direct effects of oxycodone on cancer cells. Aim: To determine the effects and mechanisms of oxycodone in cancer cells. Materials and Methods: Proliferation, survival and migration assays were performed on multiple types of cancer cells. Epithelial growth factor receptor (EGFR)/ERK/Akt pathway and oxidative stress were investigated after oxycodone treatment. Results: Oxycodone can either stimulate growth and migration without affecting survival in MDA-468 cells or inhibit growth and survival without affecting migration in SKBR3 and Caco2 cells. In addition, oxycodone can either attenuate or stimulate efficacy of chemotherapeutic drugs in cancer, depending on the type of cancer cells and nature of action of oxycodone as single drug alone. Our mechanism studies suggest that the stimulatory and inhibitory effects of oxycodone are associated with EGFR expression levels in cancer cells. In cancer cells with high EGFR level, oxycodone activates EGFR signaling in cancer cells, leading to stimulatory effects in multiple biological activities, and this is dependent on opioid receptor. In cancer cells with low EGFR level, oxycodone induces mitochondria-mediated caspase activity and oxidative stress and damage, leading to cell death. Conclusions: Our work is the first to demonstrate systematic analysis of oxycodone's effects and mechanism of action in cancer. The activation of EGFR signaling by oxycodone may provide a new guide in the clinical use of oxycodone, in particular for cancer patients with high EGFR levels.